Surgery for Extratemporal Partial Epilepsy - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1991)
The results of surgery for extratemporal partial epilepsy that began in childhood are reported from the Department of Surgery, Stanford University Medical School; Department of Neurology, University of Rochester; University of Colorado Health Sciences Center; and the Children's Hospital, Boston MA.